2019
DOI: 10.1002/acp.3609
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of other‐race effect for Chinese faces in Malaysian non‐Chinese population

Abstract: SummaryThe other‐race effect (ORE) reflects poor recognition of faces of a different race to one's own. According to the expertise‐individuation hypothesis, this phenomenon is a consequence of limited experience with other‐race faces. Thus, similar experience with own and other‐race faces should abolish the ORE. This study explores the ORE in a multi‐racial country (i.e., Malaysia) by comparing Malaysian observers' face recognition for faces of a predominant racial group in Malaysia (i.e., Chinese) with faces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
6
22
0
Order By: Relevance
“…The maximum total scores observers can get in the CFMT is 72 (i.e., one point for each correct trial). Internal reliability analysis showed an alpha value of 0.85 which is in agreement with previous research ( Estudillo et al, 2020 ; Estudillo, in press ; McKone et al, 2012 ).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The maximum total scores observers can get in the CFMT is 72 (i.e., one point for each correct trial). Internal reliability analysis showed an alpha value of 0.85 which is in agreement with previous research ( Estudillo et al, 2020 ; Estudillo, in press ; McKone et al, 2012 ).…”
Section: Methodssupporting
confidence: 91%
“…Although the CFMT was initially introduced with Caucasian faces, more recent versions have adapted the face stimuli to Chinese and South East Asian populations: the CFMT-Chinese ( McKone et al, 2012 , 2017 ). Remarkably, these two versions of the CFMT are psychometrically quite robust as they present internal reliability scores of between 0.85 and 0.90 ( Bowles et al, 2009 ; Estudillo et al, 2020 ), which is an important requirement for measures of individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Tan et al (2012) reported that Malaysian-Chinese young adults performed equally well at recognizing East Asian and Western-Caucasian faces, but less well at recognizing African faces, which are not typically encountered in Malaysia. In contrast, Estudillo et al (2019) found that Malaysians (Chinese, Malay, Indian) recognized Chinese faces equally well compared to the normative data derived from Mainland-Chinese population (Mckone et al, 2017) but showed a clear ORB for Caucasian faces. In the latter two studies, however, only Malaysian samples were involved, and conclusions were drawn without including Western-Caucasians as a comparison group.…”
Section: Malaysia As a Multiracial Countrymentioning
confidence: 60%
“…Considering its unique multiracial characteristics, Malaysia provides an interesting environment for face recognition research and a rich field area for studying ORB in the context of high interracial contact among the different race groups. Three recent studies have highlighted the unique cultural and racial diversity in Malaysia and how this can have a direct influence on face processing ability of own-and other-race faces in children (Su et al, 2017) and young adults (Tan et al, 2012;Estudillo et al, 2019). Su et al (2017) reported that Malaysian-Chinese children tested with four races of faces (Chinese, Malay, African, and Caucasian) showed reduced recognition of African faces, but similar recognition accuracy for Chinese, Malay, and Caucasian faces.…”
Section: Malaysia As a Multiracial Countrymentioning
confidence: 99%
“…Although the CFMT was initially introduced with Caucasian faces, more recent versions have adapted the face stimuli to Chinese and South East Asian populations: the CFMT-Chinese (McKone et al, 2012, 2017. Remarkably, these two versions of the CFMT are psychometrically quite robust as they present internal reliability scores of between 0.85 and 0.90 (Bowles et al, 2009;Estudillo et al, 2020), which is an important requirement for measures of individual differences.…”
Section: Introductionmentioning
confidence: 99%